UPAYA MENINGKATKAN KEMAMPUAN MENENTUKAN UNSUR INTRINSIK CERITA FANTASI DENGAN MENERAPKAN METODE INKUIRI SISWA KELAS VII A SEKOLAH MENENGAH PERTAMA NEGERI 3 TABANAN TAHUN PELEJARAN 2021/2022 - I Made Suparta; Veronika Umbu Zagora (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
The low learning ability of students in determining the intrinsic elements of fantasy stories so far is influenced by the not yet optimal implementation of learning to determine the intrinsic elements of fantasy stories. In addition, teachers have not optimally used learning methods in improving students' abilities in determining the intrinsic elements of fantasy stories. The problem in this research is how the students' abilities before and after applying the inquiry method and how much the increase. The purpose of this research is to solve the problem as stated above. This research is a classroom action consisting of two cycles with 32 students. Data collection methods used, namely the observation method and the test method. Observation method used the ability to determine the intrinsic elements of fantasy stories. The results showed that the ability to determine the intrinsic elements of fantasy stories of class VII A students of State Junior High School 3 Tabanan in the 2021/2022 academic year after applying the inquiry method had increased. This can be seen in the students' completeness in the pre-cycle with an average score of 64.38, in the first cycle the class average value of 70.32. Then in the second cycle it increased again with an average value of 82.31 students, all students have completed 100%. The increase in the score is a sign that the ability to determine the intrinsic elements of fantasy stories for Class VII A State Junior High School 3 Tabanan for the 2021/2022 academic year is getting better after applying the inquiry method in learning activities because it has been proven that the application of the inquiry method can improve students' abilities.